Investigation of the relationship between internet addiction with emotion regulation in adolescent: A cross-sectional study - Sharm, Aaras; Kappor, Priya (Science Center Group, 2025)
Background: Internet addiction has emerged as a growing behavioral concern among adolescents, often associated with emotional dysregulation and psychological distress. Adolescents are in a critical developmental stage marked by emotional instability and heightened engagement with digital technologies, making them particularly vulnerable to compulsive internet use. Difficulties in emotion regulation are thought to play a central role in reinforcing maladaptive online behaviors. This study aimed to investigate the relationship between internet addiction and emotion regulation difficulties among adolescents. Methods: A cross-sectional quantitative study was conducted among 312 adolescents aged 15–18 years from several secondary schools. Participants were selected using stratified random sampling. Data were collected using a demographic questionnaire, the Internet Addiction Scale (IAS), and the Difficulties in Emotion Regulation Scale–16 (DERS-16). Descriptive statistics, independent t-tests, one-way ANOVA, Pearson correlation, and simple linear regression were performed to analyze the data. Ethical approval and informed consent were obtained before data collection. Results: The mean IAS score was 74.6 (SD = 15.2) and the mean DERS-16 score was 46.8 (SD = 11.7), indicating moderate levels of internet addiction and emotion regulation difficulties. Males reported significantly higher internet addiction scores than females (p < 0.01), while no gender differences were found in emotion regulation scores. Pearson analysis revealed a significant positive correlation between IAS and DERS-16 scores (r = 0.56, p < 0.001). The strongest correlations were found in impulse control difficulties (r = 0.62) and limited access to emotion regulation strategies (r = 0.58). Regression analysis showed that emotion regulation difficulties significantly predicted internet addiction (β = 0.55, p < 0.001). Conclusion: Adolescents with greater difficulties in emotion regulation are more likely to experience higher levels of internet addiction. Impulse control problems and limited emotion regulation strategies appear to be the strongest emotional risk factors for compulsive internet use. These findings highlight the need to view internet addiction not only as a behavioral issue but also as an emotional regulation problem.